Enhanced piezo-photocatalysis in Bi0.5Na0.5TiO3@Ag composite to efficiently degrade multiple organic pollutants. (1st December 2022) - Wang, Peng; Yu, Fangyuan; Chi, Yuan; Wu, Xiao; Lin, Mei; Lin, Cong; Lin, Tengfei; Gao, Min; Zhao, Chunlin; Li, Xiangqi
Abstract: The synergistic piezo-photocatalysis with enhanced efficiency for degrading obstinate pollutants in wastewater is considered as an advanced way to ameliorate the global water contamination. In this work, we report a facile route to construct the Bi0.5 Na0.5 TiO3 @Ag composite by photoreduction of AgNO3 to obtain Ag on Bi0.5 Na0.5 TiO3 nanoparticles. And the composite was used to degrade three representative pollutants, i.e. ciprofloxacin, methyl orange and mitoxantrone hydrochloride. Remarkably, for methyl orange solution with the initial concentration of 10 mg/L, the degradation rate constant of the composite reached 0.051 min −1 . H + and O2 − play a major role in this degradation process, verified by the radical quenching experiments. The absorption platform of Bi0.5 Na0.5 TiO3 was located in the UV region, after introducing Ag in the composite, the absorption region broadened to both UV and visible light, greatly promoting the response to light. Simultaneously, the induced piezo-potential by mechanical energy in Bi0.5 Na0.5 TiO3 hindered the carrier recombination, resulting in high-efficiency synergistic piezo-photocatalytic process. This work provides a paradigm to innovate both material and catalytic way for degrading multiple organic pollutants. Highlights: BNT@Ag composite was constructed by direct addition of AgNO3 . Efficient piezo-photocatalytic synergistic effect was achieved. Absorb both UV and visible light for higher utilization ratio of light energy. Maintain good catalytic performance in varying environment.